Evaluation of Left ventricular systolic function by Myocardial Deformation Imaging in Hypertensive patients with Preserved Left Ventricular Ejection Fraction - Baral, Bishow Raj; Maskey, Arun; Malla, Rabi; Rajbhandari, Sujeeb; Adhikari, Krishna Chandra; Bhandari, Shreya; Shrestha, Shipra; Pandey, Rabindra; Shimkhada, Rabindra; Budhathoki, Arjun (Nepalese Heart Journal, 2021)
Background and Aims: Hypertension being one of the commonest non communicable diseases is major risk factor leading to premature death.1 With development of, the left ventricular strain imaging technique by echocardiography the consequences of hypertension may be identified and intervene earlier. The aim of study was to show abnormalities in cardiac function in the form of left ventricular strain imaging in hypertensive patients with preserved Ejection fraction. Methods: This was a cross-sectional, comparative and observational study done in Shahid Gangalal National Heart Centre and National Academy of Medical Sciences, Bir Hospital Kathmandu which included hypertensive patients with baseline examination including a medical history, clinical examination and a standardized trans thoracic echocardiography and strain imaging examination and the findings were compared among age and sex frequency matched 82 healthy adults in 1 : 2 ratio. The independent paired t test was used for the comparative statistical analysis. Results: We enrolled 240 patients in this study, 158 were hypertensive (mean age 48.5 ±6.1 years with 50.6 % female) and 82 healthy control (mean age 45.62 ±6.3 years with 51.2% female). There was no significant difference in conventional echocardiographic parameters between two groups except for left ventricular mass index and relative wall thickness that was highest in hypertensive group (p value of <0.001). The hypertensive population has lower mean global longitudinal strain (GLS) value of -18.6% ± 2.06 SD compared to the healthy control population with mean of -19.5% ± 1.1 SD (p value of <0.001). Conclusion: Hypertensive patients with preserved left ventricular ejection fraction have subclinical left ventricular dysfunction revealed by GLS imaging technique.